2021
DOI: 10.1039/d0md00370k
|View full text |Cite
|
Sign up to set email alerts
|

Put a ring on it: application of small aliphatic rings in medicinal chemistry

Abstract: Aliphatic small rings including cyclopropanes, cyclobutanes, oxetanes, azetidines and bicyclo[1.1.1]pentanes have been increasingly exploited in medicinal chemistry. This review summarises judicious successful application and reported limitations of these ring systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
152
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(174 citation statements)
references
References 177 publications
1
152
0
Order By: Relevance
“…Numerous studies, including those carried out over the years by our group, show that thiazole derivatives have high antifungal activity [3,25]. The cyclopropane system, due to its unique properties, such as low molecular weight, conformational rigidity, unusual bonding and planarity, is used in drug design as a replacement for gem-dimethyl and alkene groups and phenyl rings, leading to the reduced lipophilicity and increased metabolic stability of drugs [26,27]. We have recently shown that thiazole derivatives containing a cyclopropane ring exhibit high activity against both reference strains and clinical isolates of Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies, including those carried out over the years by our group, show that thiazole derivatives have high antifungal activity [3,25]. The cyclopropane system, due to its unique properties, such as low molecular weight, conformational rigidity, unusual bonding and planarity, is used in drug design as a replacement for gem-dimethyl and alkene groups and phenyl rings, leading to the reduced lipophilicity and increased metabolic stability of drugs [26,27]. We have recently shown that thiazole derivatives containing a cyclopropane ring exhibit high activity against both reference strains and clinical isolates of Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…These BCP derivatives serve as bioisosteres for arenes, internal alkynes, and tert-butyl groups in medicinal chemistry settings. 35 With respect to the scope of triuoromethyl-substituted alkenes, a diverse array of DNA headpieces (DNA-HPs) led to the desired benzylic triuoromethyl-substituted products without compromising yields (Scheme 4). In general, both electron-withdrawing and electron-donating groups are well tolerated under the developed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These BCP derivatives serve as bioisosteres for arenes, internal alkynes, and tert -butyl groups in medicinal chemistry settings. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Some representative natural cyclobutenes such as cyclomegistine or β‐lumicolchicine are depicted in Scheme 1a. Due to the highly rigid backbone and the well‐defined three‐dimensional rearrangement of the substituents, these scaffolds are privileged in medicinal chemistry [1f] . They can also be considered as key building blocks for the synthesis of highly substituted cyclic, heterocyclic or acyclic derivatives, via ring expansion, ring contraction or rearrangements [2] .…”
Section: Methodsmentioning
confidence: 99%